Study on fibonacci patterns in monocots and dicots ornamental plants / Nazirah Ramli, Neni Kartini Che Mohd RamIi and Amirah Hana Mohamed Nor - Ramli, Nazirah; Che Mohd RamIi, Neni Kartini; Mohamed Nor, Amirah Hana (2011)
The Fibonacci sequence 1, 1, 2, 3, 5, 8, 13, 21, 34, ... has many remarkable properties, ranging from routine to startling. This ever-growing and endless chain of numbers can be used to explain the occurrence of many things in nature, such as the arrangement of petals and seeds in flowers, proportions of the human body, the shape of a snail shell and others. This study investigates the existence of Fibonacci patterns in monocot and dicot types of ornamental plants. The results show that most of the ornamental plants with petals in Fibonacci patterns are dicots.